The Implementation of Job Safety and Occupational Health at PT. Wijaya Karya, based on Characteristics of Worker - Delicia Angow; Candra Irawan; Mariatul Kiptiah (Civil Engineering Dept, Balikpapan State Polytechnics, 2002)
Occupational health and safety is one important aspect in a company so that the company can minimize a work accident, where in case of a work accident then it can hamper the productivity of employees. The purpose of this study is to determine the application of occupational safety and health on the productivity of employees and how the influence of which is given of the application. This research method using quantitative analysis with the data analysis technique used is the analysis of descriptive statistics. In the analysis descriptive statistics variable values obtained for the variable health & Safety is equal to 3.62 which means very high then on the productivity variable that is equal 3,47 that is very high. It can be concluded that has been conducted on the application of occupational safety and health thereby increasing employee productivity.